Peran KPAD Kota Tasikmalaya Dalam Memberikan Layanan Edukasi, Psikologi Dan Hukum Anak Dibawah Umur - Huriyah, Fauziah Syarifatul; Gandana, Gilar; Hashipah, Hani; Aisyahni, Nur Laela; Rismyanti, Sri Ayu (Universitas Hamzanwadi, 2024)
Education, psychology, and legal protection of minors are the main focus in safeguarding children's rights and development. This article highlights the role of the Regional Child Protection Commission (KPAD) of Tasikmalaya City in providing these services. Through qualitative methods, case studies, and descriptive methods, this article evaluates 2023 children's cases in Tasikmalaya City and KPAD's efforts in providing educational, psychological, and legal services. As a result, of the 34 cases recorded, violence in the form of various cases became the main highlight. However, the fight for child custody, access to meet children, and sexual abuse are the most dominant. KPAD's service program consists of education, psychological assistance, and legal assistance. Educational counseling, psychological assistance, and legal assistance are the main pillars of the service. Through a holistic approach, KPAD Tasikmalaya City presents services that include aspects of education, mental health, and legal protection. With various strategies, such as seminars, socialization, and group guidance, KPAD strives to provide concrete solutions for children in need. The process of planning, implementing, and evaluating programs is key in ensuring the effectiveness and sustainability of services.